Optimalisasi fungsi manajemen kepala ruangan dalam supervisi klinik menggunakan alat bantu Google form di rumah sakit di Jakarta - Neni Triana; Enie Novieastari; Satinah Satinah (Holistik Jurnal Kesehatan, 2020)
Utilization of digital technologies as a strategy to optimizing management functions in nursingBackground: Nursing services need a good management of Nurse Managers to achieve a standardized service quality. Clinical supervision nursing has generally been implemented in hospitals, but its application has not been implemented optimally causing quality improvement not to run continuously.Purpose: To identify issues of implementation clinical supervision nursing and to develop problem-solving solutions.Method: The mini project, analysis of results and implementation gap with discussion based on literature review. Problems were analyzed using a fishbone diagram. Problem solving using Plan Do Study Action (PDSA) tools starts from Plan of Action (POA), implementation, evaluation, and follow up. The sample was taken from 5 the inpatient wards.Results: The problem identification found not optimal the quality  of nursing in the planning, monitoring and follow-up phase. Implementation of problem solving by workshop and socialization of guidance, procedure, dictionary and instrument of monitoring clinical supervision nursing with digital tecnology google form. The evaluation result shows that 100 % said the clinical form supervision of digital technology based on google form was very effective and efficientKeywords: Utilization; Digital technologies; Strategy; Optimizing; Management functions; NursingPendahuluan: Pelayanan keperawatan memerlukan pengelolaan yang baik dari Manajer Perawat untuk mencapai kualitas pelayanan keperawatan yang sesuai standar. Supervisi klinik keperawatan pada umumnya telah dilaksanakan oleh manajer keperawatan, namun penerapannya belum dilaksanakan secara optimal yang menyebabkan supervisi klinik keperawatan tidak berjalan secara berjenjang.Tujuan: Mengidentifikasi masalah pelaksanaan supervisi klinik keperawatan di ruang rawat serta mengembangkan solusi pemecahan masalah.Metode: Berupa mini project serta analisis hasil dan gap implementasi dengan pembahasan berdasarkan literature review. Masalah dianalisis menggunakan diagram fishbone. Penyelesaian masalah menggunakan tools Plan Do Study Action (PDSA) dimulai dari Plan of Action (POA), implementasi, evaluasi, dan tindak lanjut. Sampel diambil dari ruang rawat inap yang terdiri dari 5 Kepala Ruangan.Hasil: Ditemukan tidak optimalnya supervisi klinik keperawatan pada tahap perencanaan, pemantauan dan tindak lanjut. Implementasi pemecahan masalah berupa sosialisasi dan workshop supervisi klinik keperawatan berbasis teknologi digital google form. Hasil evaluasi menunjukkan bahwa  100 % mengatakan supervisi klinik keperawatan berbasis teknologi digital google form sangat efektif dan efesien.